Reception of Dostoevsky’s Creativity in Chinese Translations, Works of Art and Scientific Research - Huirong Ai (Научный диалог, 2020)
The article is devoted to a survey analysis of F. M. Dostoevsky’s reception in the works of fiction of Chinese writers and in scientific literary studies. The main features of the translations of Dostoevsky’s texts and studies of the Russian classic in different historical periods, which were determined by the socio-cultural attitudes and ideological orientation that dominate in China, are considered. It is noted that the representation of Dostoevsky in China from the very beginning was not an exclusively cultural phenomenon, but was associated with the desire of the progressive intellectuals to create a modern national literature. Based on historical facts and scientific research, it is established that Dostoevsky’s reception is represented in the artistic world of modern Chinese writers of  different generations, in particular Lu Xun, Yu Dafu, Tie Ning and many others, but deep comparative studies have been carried out only in relation to writers of the 1920s and 1940s years. The author pays special attention to the analysis of the political and cultural background and ideological attitudes in the perception of Dostoevsky’s creativity and views by Chinese writers. It is shown that Dostoevsky’s reception in China is pragmatic and one-sided: Chinese writers highly appreciated Dostoevsky’s humanistic attitude towards the “humiliated and insulted”, but generally did not accept his religious ideas.